Impact of the zero‐markup drug policy on hospitalisation expenditure in western rural China: an interrupted time series analysis. Issue 2 (18th December 2016) - Yang, Caijun; Shen, Qian; Cai, Wenfang; Zhu, Wenwen; Li, Zongjie; Wu, Lina; Fang, Yu
Abstract: Objectives: To assess the long‐term effects of the introduction of China's zero‐markup drug policy on hospitalisation expenditure and hospitalisation expenditures after reimbursement. Methods: An interrupted time series was used to evaluate the impact of the zero‐markup drug policy on hospitalisation expenditure and hospitalisation expenditure after reimbursement at primary health institutions in Fufeng County of Shaanxi Province, western China. Two regression models were developed. Monthly average hospitalisation expenditure and monthly average hospitalisation expenditure after reimbursement in primary health institutions were analysed covering the period 2009 through to 2013. Results: For the monthly average hospitalisation expenditure, the increasing trend was slowed down after the introduction of the zero‐markup drug policy (coefficient = −16.49, P = 0.009). For the monthly average hospitalisation expenditure after reimbursement, the increasing trend was slowed down after the introduction of the zero‐markup drug policy (coefficient = −10.84, P = 0.064), and a significant decrease in the intercept was noted after the second intervention of changes in reimbursement schemes of the new rural cooperative medical insurance (coefficient = −220.64, P < 0.001). Conclusions: A statistically significant absolute decrease in the level or trend of monthly average hospitalisation expenditure and monthly average hospitalisation expenditure after reimbursement was detected after the introduction of the zero‐markup drug policy in western China. However, hospitalisation expenditure and hospitalisation expenditure after reimbursement were still increasing. More effective policies are needed to prevent these costs from continuing to rise.